Organisational and neuromodulatory underpinnings of structural-functional connectivity decoupling in patients with Parkinson’s disease - Angeliki Zarkali (Nature Portfolio, 2021)
Zarkali et al. identify two organizational gradients to structural-functional connectivity decoupling in Parkinson’s disease and relate spatial patterns of decoupling to the expression of neurotransmitter receptors. This study provides a framework that explains the specific disorders of consciousness in Parkinson’s dementia and its related neurotransmitter system.